Cancer Stem Cells in Pediatric Sarcomas - Dela Cruz, Filemon S. (Frontiers in Oncology, 2013)
Sarcomas represent a clinically and biologically diverse group of malignant connective tissue tumors. Despite aggressive conventional therapy, a large proportion of sarcoma patients experience disease recurrence which will ultimately result in mortality. The presence of a unique population of cells, referred to as cancer stem cells (CSC), have been proposed to be responsible for refractory responses to current chemotherapies as well underlying the basis for metastasis and relapse of disease - clinical corollaries to what has been termed the cancer stem cell hypothesis. The presence of CSCs have been suggested in a variety of hematologic and solid malignancies, and only more recently in sarcomas. Based on our current understanding of normal stem cell biology and evidence obtained from the study of malignant hematopoietic and solid tumors, researchers have identified candidate cell surface markers (CD133, CD117, Stro-1), biochemical markers (aldehyde dehydrogenase activity), and cytological characteristics (side population and spherical colony formation) that may identify putative sarcoma CSCs. In this review, we explore the current state of evidence that may suggest the existence of sarcoma CSCs. We present research in osteosarcoma, the Ewing’s sarcoma family of tumors, rhabdomyosarcoma, as well as other sarcoma subtypes to describe commonly used molecular and biochemical markers, as well as techniques, used in the identification, isolation and characterization of candidate sarcoma CSCs. We will also discuss the current controversies and challenges that face research in sarcoma CSC.